The influence of menstrual cycle in heart rate variability and performance - a case study of a highly-trained female long-distance runner - Barría-Miranda, F.; Azócar-Gallardo, J.; Ñancupil-Andrade, L.; Ñancupil-Andrade, A.; Garcia-Carrillo, E.; Campos-Uribe, V.; Cresp-Barria, M. (Journal of Human Sport & Exercise, 2025)
Introduction: Heart rate variability (HRV) is a non-invasive marker of the autonomic nervous system (ANS) that provides insights into physiological responses to training. This study investigates the relationship between HRV and athletic performance with and without the menstrual cycle (MC) in a highly-trained female long-distance runner. Methods: A 24-year-old elite female long-distance runner participated in this quantitative case study. HRV was recorded daily using a Polar H10 chest strap over three months, both with and without the MC. Athletic performance was assessed through mean power output (MPO) during 3-minute time trials (TT) using a Stryd inertial sensor. Four evaluations were conducted: two without MC and two with MC. Results: A nearly perfect correlation was found between HRV (rolling RMSSD) and MPO during the first TT without MC (r = 0.969, p = .001). However, no significant correlations were observed during the second TT with MC, the third TT without MC, or the fourth TT with MC. These findings suggest that HRV is a reliable marker for predicting athletic performance in the absence of MC but is influenced by hormonal fluctuations during the MC. Conclusion: HRV monitoring is a valuable tool for assessing internal load and predicting performance in female athletes. However, its reliability can be affected by the menstrual cycle and by accumulated fatigue. Future research should explore larger sample sizes and the impact of contraceptives on HRV and performance.